Viewpoint: Responding to Destructive Interpersonal Interactions: A way forward for School-Based Environmental Educators - Alistair Chadwick (Environmental Association of Southern Africa, 2004)
This viewpoint paper focusses on the interpersonal problems that result in an unhealthy/unsafe school environment. Within the Southern African Development Community (SADC) region, the prevalence of domestic violence, child abuse, sexism, cultural intolerance and other destructive interpersonal interactions and relationships clearly indicate an unsustainable society; one that prevents complete health amongst its members. Of further concern is the fact that these issues have not only been shown to have a marked negative impact on the ability of young people to learn but also to engage meaningfully with peers in the classroom/school environment. This paper highlights the need for dialogue and reflection around the emotions that are often evoked by the above issues. It also argues the need for whole-school structures and procedures as crucial aspects of any response to these problems. In this regard, it suggests that the values promoted by many of the SADC states might serve as a foundation for the development of such a response.